Faktor-Faktor Yang Mempengaruhi Agresivitas Pajak - wayan, pande (Jurnal Pendidikan Indonesia, 2022)
The purpose of this study was to determine the effect of capital intensity, leverage, and corporate social responsibility on tax aggressiveness with corporate governance as a moderating variable. This research was conducted on Healthcare companies listed on the Indonesia Stock Exchange for the period 2019-2021. The number of samples in this study was 36 samples using the purposive sampling method in sampling. The data used are in the form of annual report data and financial statements of health companies listed on the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear analysis with the STATA program. The results show that capital intensity has a positive effect on tax aggressiveness